Pengaruh Model Supervisi Klinik Terhadap Kinerja Asuhan Keperawatan di Instalasi Rawat Inap 2 RS TNI Jakarta - Handayani Sitorus (Cindoku : Jurnal Keperawatan dan Ilmu Kesehatan, 2024)
Nursing services are part of health services that contribute significantly to achieving development goals in the health sector. Nursing is a profession and nurses as professionals are responsible for providing quality nursing services with their competence and authority (Ksouri, 2010; Supratman, 2008). The Objective this study is to find out the influence of the clinical supervision model on the performance of nurses in nursing care in inpatient installation 2 of the TNI Jakarta Hospital. The subjects in this study were 88 nurses and 92 documentation files according to the inclusion criteria. This study uses the Quasi Experiment method and is analyzed including univariate, bivariate and multivariate. Data collection uses training and questionnaires. Research results there was an increase in the performance of nurses in nursing care in 2 TNI Jakarta Hospitals with  a pvalue of 0.000.